Value of project management in university–industry R&D collaborations. Issue 4 (12th March 2020) - Fernandes, Gabriela; O' Sullivan, David; Pinto, Eduardo B.; Araújo, Madalena; Machado, Ricardo J.
Abstract : Purpose: University–industry projects provide special challenges in understanding and expressing the values required of project management (PM) in delivering stakeholder benefits. This paper presents a framework for understanding, identifying and managing the values of PM in major university–industry R&D projects. Design/methodology/approach: The value framework identifies for each of the key stakeholders, the key PM values that may require to be managed and are largely derived from research literature. Empirical research then explores, prioritises and selects key PM values that need to be managed for a specific project. A large case study is used involving one university and one industry collaborating on a multi-million Euro initiative over six years. Empirical research was conducted by researchers who observed at close quarters, the challenges and successes of managing the competing values of key stakeholders. Findings: The value framework takes a stakeholders' perspective by identifying the respective PM values for each of six stakeholders: university–industry consortium, university, industry, R&D external entities, funding entity and society. Research limitations/implications: The research was performed using only one case study which limits the generalisability of its findings; however, the findings are presented as a decision support aid for project consortia in developing values for their own collaboration. Practical implications: Guidance and decision support are provided to multi-stakeholder research consortia when selecting values that need to be managed for achieving tangible and intangible project benefits. Originality/value: The paper demonstrates a proposed framework for designing and managing the value of PM in large multi-stakeholder university–industry R&D projects.